Communicating bad news: ethical dilemmas before situations of encephalic death - dos Santos, Marcelo José; Leal de Moraes, Edvaldo; Komatsu Braga Massarollo, Maria Cristina (O Mundo da Saúde, 2012)
Communicating the diagnosis of encephalic death is a difficult task and must precede the request for organ and tissue donation for transplant. This situation may arouse ethical dilemmas permeated by religious, spiritual, cultural, economic and / or social factors. This paper aims to explain the reader about the historical and epidemiological aspects of encephalic death and to present some ethical dilemmas faced by families of potential donors after the announcement of that bad news.